ปัญหาในการบริหารงานฝึกอบรมแก่พนักงาน : ศึกษาเฉพาะกรณีการไฟฟ้านครหลวง - ทนง ทองเต็ม (จุฬาลงกรณ์มหาวิทยาลัย, 1980)
The Metropolitan electricity authority is a government enterprise that is responsible for providing and serving electricity for people in the metropolitan area. Nowsadays there are 5,000,000 users in Bangkok city, Nonthaburi province, Samutprakarn province and some parts of Phrathumthanee province. According to the amount of consumers and the highly dynamic of environmental changes in community, government and technology, the MEA confronts the problems how to serve the users efficiently. One of the most important means to solve those problems is the personnel training which will increase knowledge, experience and skill in serving the users together with the realization in correct attitude and behavior in serving the users. The concept in this research is originated from the role of the researcher who is one of the training officers in the division of training and development. The researcher has observed the process of training and realized some problems, therefore the objective of this title has been formulated in order to solve the problems. The methods of collection data are concentrated in interviewing and questioning both the training officers and the trainees for the purpose of comparing the result. The research has come up with the following conclusions: a. Problems of general administration in the division of training and development 1) Problem of the quantity of personnel 2) Problem of training planning 3) Problem of training and development for training officers 4) Problem of the training organizing 5) Problem of controlling b. Problems of training administration for personnels 1) Problem of training need analysis 2) Problem of objective setting 3) Problem of program design 4) Problem of implementation 5) Problem of follow up and evaluation Reccommendation for problem solving 1. Improving the structure of the division of training and development, to meet the increasing quantity of work load, for the purpose related to the personnel planning of MEA. In the future. 2. Improving the process of training administration as a system pertinent to the process of training and development. The details of conclusion and recommendation are indicated in chapter 6.